2022
DOI: 10.1371/journal.pone.0277053
|View full text |Cite
|
Sign up to set email alerts
|

Human CYP2B6 produces oxylipins from polyunsaturated fatty acids and reduces diet-induced obesity

Abstract: Multiple factors in addition to over consumption lead to obesity and non-alcoholic fatty liver disease (NAFLD) in the United States and worldwide. CYP2B6 is the only human detoxification CYP whose loss is associated with obesity, and Cyp2b-null mice show greater diet-induced obesity with increased steatosis than wildtype mice. However, a putative mechanism has not been determined. LC-MS/MS revealed that CYP2B6 metabolizes PUFAs, with a preference for metabolism of ALA to 9-HOTrE and to a lesser extent 13-HOTrE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 105 publications
0
16
0
Order By: Relevance
“…S4A, B and C †), suggesting that AMPK is the upstream protein of SIRT1 and is positively correlated with it. It has been shown that 13-OxoODE is an activator of PPARα 52 and can affect PPARα expression; while nicotinamide affects lipid metabolism by increasing fatty acid β-oxidation activity. 53 Here, 13-OxoODE and nicotinamide were significantly…”
Section: Discussionmentioning
confidence: 99%
“…S4A, B and C †), suggesting that AMPK is the upstream protein of SIRT1 and is positively correlated with it. It has been shown that 13-OxoODE is an activator of PPARα 52 and can affect PPARα expression; while nicotinamide affects lipid metabolism by increasing fatty acid β-oxidation activity. 53 Here, 13-OxoODE and nicotinamide were significantly…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have related CYP7A1 to lipid metabolism (Wang et al, 2020;Lyu et al, 2022), which highlights the importance of our study when verifying that the diet with oils modified the expression in pigs. In humans, CYP2B6 is the only hepatic isoform of CYP2B that plays a role in the metabolism of numerous xenobiotic and endobiotic compounds (Heintz et al, 2022). Cholesterol and dietary fats modulate CYP7A1 activity and gene expression in humans, but the exact mechanism by which fatty acids can regulate CYP7A1 expression remains to be elucidated (Fu et al, 2011).…”
Section: Process Network P-value Degmentioning
confidence: 99%
“…Mice that lack the three primarily hepatic Cyp2b members, Cyp2b9, Cyp2b10, and Cyp2b13 (Cyp2b-null or Cyp2b9/10/13-null) show greater susceptibility to high-fat diet induced obesity coupled with increased steatosis in males [44,57]. The presence of human CYP2B6 in Cyp2b-null mice (hCYP2B6-Tg) reduced obesity in the females; however suprisingly, human CYP2B6 increased steatosis in association with several oxylipins including 9-HODE and 13-KODE from linoleic acid, and 12,13-DHET, 14,15-EET, and 14,15-DHET from arachidonic acid [8]. Whether these oxylipins are directly involved in obesity or steatosis is unknown.…”
Section: Cyp Expression Obesity and Oxylipinsmentioning
confidence: 99%
“…Products produced include the thromboxanes, prostaglandins, leukotrienes, lipoxins, and the less studied and more recently measured CYP-derived oxylipins such as the epoxides and diols produced from those epoxides by soluble epoxide hydrolase (sEH). These oxylipins may have powerful activity at multiple receptors [3]; however, some oxylipins have little function or no verified function and the roles of several oxylipins have been poorly defined [1,8].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
See 1 more Smart Citation